2006
DOI: 10.5194/acp-6-2241-2006
|View full text |Cite
|
Sign up to set email alerts
|

The North Atlantic Marine Boundary Layer Experiment(NAMBLEX). Overview of the campaign held at Mace Head, Ireland, in summer 2002

Abstract: Abstract. The North Atlantic Marine Boundary Layer Experiment (NAMBLEX), involving over 50 scientists from 12 institutions, took place at Mace Head, Ireland (53.32 • N, 9.90 • W), between 23 July and 4 September 2002. A wide range of state-of-the-art instrumentation enabled detailed measurements of the boundary layer structure and atmospheric composition in the gas and aerosol phase to be made, providing one of the most comprehensive in situ studies of Correspondence to: D. E. Heard (dwayneh@chem.leeds.ac.uk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…However, the semi-polluted NO x regime at Roscoff is, as noted by Mahajan et al (2009), rather different from that for previous I 2 measurements at cleaner background sites, most notably at the Mace Head Atmospheric Research Station (Galway, Ireland) where typical NO 2 concentrations (Heard et al, 2006) are below the minimum NO 2 levels observed during RHaMBLe and thus little recycling of I 2 via IONO 2 chemistry is expected.…”
Section: Modelling)mentioning
confidence: 55%
See 1 more Smart Citation
“…However, the semi-polluted NO x regime at Roscoff is, as noted by Mahajan et al (2009), rather different from that for previous I 2 measurements at cleaner background sites, most notably at the Mace Head Atmospheric Research Station (Galway, Ireland) where typical NO 2 concentrations (Heard et al, 2006) are below the minimum NO 2 levels observed during RHaMBLe and thus little recycling of I 2 via IONO 2 chemistry is expected.…”
Section: Modelling)mentioning
confidence: 55%
“…The BBCRDS system used for this study is based on an instrument previously used to measure I 2 at Mace Head (Ireland) during the 2002 NAMBLEX campaign Heard et al, 2006) as described in detail by Bitter et al (2005). In the intervening years, the instrument's performance has been enhanced significantly by upgrading several key components, notably a new laser system that yields pulsed broadband light with a factor of two wider bandwidth at green wavelengths, a new clocked CCD camera and improved analysis software/spectral fitting routines.…”
Section: Bbcrds Measurementsmentioning
confidence: 99%
“…1). The research station has been the subject of extensive halogen studies in the past (e.g., Alicke et al, 1999;Saiz-Lopez et al, 2006a) and is described extensively in Heard et al (2006).…”
Section: Site Descriptionmentioning
confidence: 99%
“…3h) peaks at lower values compared to the other classes. A near-surface RH w around 85% is typical for marine boundary layers (e.g., Heard et al 2006), resulting from a balance between the surface flux over open water, precipitation, and entrainment of dry air near PBL top.…”
Section: A Surface and Near-surface Variablesmentioning
confidence: 99%